The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4103/0974-9233.92115
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of exudative age-related macular degeneration treatment

Abstract: Treatment of exudative age-related macular degeneration has been revolutionized within the last 6 years with the introduction of vascular endothelial growth factor neutralizing agents. Previously popular “destructive treatments,” such as laser photocoagulation and photodynamic treatment have either been abandoned or used as an adjunct to pharmacotherapy. Despite the increase in vision after antivascular endothelial growth factor (VEGF) agents, they require repetitive and costly intravitreal injections that als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To date, PDT using Visudyne ® has saved the vision of millions of patients with retinal pathologies, and has been shown to work even more effectively using combination strategies. 26 As discussed earlier, the liposomal PNM formulation Visudyne ® pushes the boundaries of typical nanotherapeutics in that it enables the regulation of spatiotemporal control over treatment induction, and thus bears huge clinical potential with regards to the impact this regulated approach can have on combination cancer therapies. 8, 27 The immediate clinical impact of Visudyne ® is further evidenced in the ongoing clinical trials for pancreatic cancers.…”
Section: Clinical Nanomedicinementioning
confidence: 99%
“…To date, PDT using Visudyne ® has saved the vision of millions of patients with retinal pathologies, and has been shown to work even more effectively using combination strategies. 26 As discussed earlier, the liposomal PNM formulation Visudyne ® pushes the boundaries of typical nanotherapeutics in that it enables the regulation of spatiotemporal control over treatment induction, and thus bears huge clinical potential with regards to the impact this regulated approach can have on combination cancer therapies. 8, 27 The immediate clinical impact of Visudyne ® is further evidenced in the ongoing clinical trials for pancreatic cancers.…”
Section: Clinical Nanomedicinementioning
confidence: 99%
“…Despite such interventions aiming to inhibit further pathological angiogenesis, some studies have demonstrated that they play no active role in reestablishing an optimum interface between the principle ocular regions required for central vision [ 38 ]. Rather, such treatments, at best, lead to the formation of a disciform scar which only augments the loss of vision due to its physical presence disrupting the above interface.…”
Section: Future Treatments For Neovascular Amdmentioning
confidence: 99%
“…Rather, such treatments, at best, lead to the formation of a disciform scar which only augments the loss of vision due to its physical presence disrupting the above interface. In addition to this, present treatments only provide therapeutic benefit to those with the active form of neovascular AMD, therefore being futile and redundant for those who have already lost their vision [ 38 ]. With such significant limits, further research is being conducted on novel options which address the aforementioned issues.…”
Section: Future Treatments For Neovascular Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed previously, anti-VEGF drugs are the most common drugs used in the treatment of AMD [ 180 ], and recent studies utilizing nanoemulsion and polymeric micelle delivery of these drugs continue to show improved clinical utility. Polymeric micelles containing the anti-VEGF drug EYE001 and bevacizumab both resulted in sustained delivery eye for AMD treatment [ 181 , 182 ].…”
Section: Nanotechnology For Dosage Optimizationmentioning
confidence: 99%